PERANAN FAKTOR-FAKTOR PSIKOLOGIS TERHADAP DEPRESI PADA DIABETES MELLITUS TIPE 2 (DM-2) - , Jenita Doli Tine Donsu ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Diabetes Mellitus is considered as a chronic disease, because the body cannot produce or use the insulin effectively. One of the ways to minimize the complication is by avoiding depression. Depression is a mental disorder that could be suffered by most of all societies, and this case has acquired intense notice from every kind of sciences. The patient who suffers diabetes because of the depression, will be possible to get the depression again, even five times more serious than the previous depression. The individual who got diabetes mellitus, usually experience the escalation of glucose that cause the ascension of cortisole, epinefrin, and norepinefrin, and all of these hormones could cause depression. The individual who is suffering diabetes mellitus has possibility to suffer depression. Depression has strong relationship with diabetes mellitus, and the psychological aspect as the control towards diabetes. This research aims to know the roles of psychological aspects based on the models which are proposed, and how to see the dynamics of direct relationship or even indirect relationship among the psychological factors towards the depression to the patients DM-2. Psychological factors play a role as a mediator of the relationship between social support with depression in patients with DM-2. The main model is a model that is able to provide a mediating effect between social support and depression in DM-2. Optimism is able to provide the mediating effect of the relationship between social support and self-esteem. Resilience is able to provide the mediating effect of the relationship between social support and self-esteem. Similarly, self-esteem acts as a mediator of the relationship between optimism and resilience against depression in patients with DM-2. Psychological dynamics of relationships based on test results concluded that the hypothesis, the hypothesis is accepted. The results of the estimation of test parameters, there is a direct role between social support on optimism (0.717), resilience (0.811), self-esteem (0.269) and depression (-0.210) and indirect role against depression (-0.397). There is a role with a positive relationship between social support on optimism, resilience and self-esteem is, the higher the social support will be more optimistic and resilient, and feel a sense of self-esteem. On the other hand, the role of self-esteem to depression showed a negative coefficient is, the higher the self-esteem will be followed by the decrease of depression in patients with DM-2.